Container Terminals and Automated Transport Systems Logistics Control Issues and Quantitative Decision Support - Günther, Hans-Otto.; Kim, Kap Hwan.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Container transportation is the predominant mode of inter-continental cargo traffic. Since container ships and port terminals involve a huge capital investment and significant daily operating costs, it is of crucial importance to efficiently utilize the internal resources of container terminals and transportation systems. Today there is an ongoing trend to use automated container handling and transportation technology, in particular, in countries with high labour costs. This in turn requires highly sophisticated control strategies in order to meet the desired performance measures. The primary objective of this book is to reflect these recent developments and to present new insights and successful solutions to operational problems of automated container terminals and transportation systems. It comprises reports on the state of the art, applications of quantitative methods, as well as case studies and simulation results. Its contributions are written by leading experts from academia and business. The book addresses practitioners as well as academic researchers in logistics, transportation, and management.
Container Terminals -- Container terminal operation and operations research — a classification and literature review -- Comparison of vehicle types at an automated container terminal -- Simulation-based performance evaluation of transport vehicles at automated container terminals -- Generating scenarios for simulation and optimization of container terminal logistics -- Fleet sizing and vehicle routing for container transportation in a static environment -- The berth allocation problem: models and solution methods -- A scheduling method for Berth and Quay cranes -- A beam search algorithm for the load sequencing of outbound containers in port container terminals -- A general framework for scheduling equipment and manpower at container terminals -- Dispatching multi-load AGVs in highly automated seaport container terminals -- Transportation Systems -- Scheduling vehicles in automated transportation systems -- Modeling of capacitated transportation systems for integral scheduling -- Modeling and optimization of the intermodal terminal Mega Hub -- A dispatching method for automated guided vehicles by using a bidding concept -- Scheduling railway traffic at a construction site -- Container Loading -- A bottleneck assignment approach to the multiple container loading problem.
Keywords: Production management; Operations research; Decision making; Engineering economics; Engineering economy; Operations Management; Operations Research/Decision Theory; Engineering Economics, Organization, Logistics, Marketing